Syndrome of duodenal compression by the superior mesenteric artery following restorative proctocolectomy: a case report and review of literature - Matheus, Claudio de Oliveira; Waisberg, Jaques; Zewer, Maria Helena de Toledo; Godoy, Antonio Claudio de (São Paulo Medical Journal, 2005)
CONTEXT: Resloralive proctocolectomy with anastomosis oi an ileal pouch to lhe anal canal is a new and rare cause for triggering the syndrome oi duodenal compression bythe superior mesenteric artery. Restorative proctocolectomy requires assessmenl oi lhe posilion oi lhe duodenum in relation to aortomesenteric constriction to avoid the occurrence oi duodenal compression by the superior mesenleric arlery. CASE REPORT: lhe authors repari on a case oi this syndrome in a patient with Iam ilial adenomatous polyposis and review lhe I ileralure on the etiopathogenesis, diagnosis, treatment and prevenlion oi this unusual entity.